An Investigation of teacher talk and student talk in Indonesian EFL Classroom Interaction - Dahia Alqalbi Nursehag; Lulu Laela Amalia (PAEDAGOGIA, 2024)
Several research studies have explored how teachers and students communicate in a classroom setting. Balancing talking time whether teacher-dominant or student-dominant during the learning process and the quality of interaction in the classroom is a challenge faced in teaching methodology even in Indonesia. The primary focus of this particular research was to examine the different types of communication, both from teachers and students, in an EFL Indonesian classroom. Additionally, the study aimed to determine the proportion of verbal interaction during the learning process. This descriptive qualitative research gathered data through observations and interviews with the participants consisting of a teacher and secondary school students, selected using a purposive sampling technique. The data collection used observation and interviews. The result of classroom interaction observation was analyzed by using Flander’s Interaction Analysis Categories (FIAC). The findings showed that teacher talk dominated the classroom interaction, accounting for 74.4% of the overall communication. Within the teacher talk category, lecturing was the most frequently used method, making up 30.3% of the interactions. On the other hand, students primarily engaged in the student talk response category, comprising 9.6% of the interactions. These observations led to the conclusion that the teacher played a dominant role in the classroom, relying heavily on lectures, while students' participation was mostly limited to responding to the teacher's questions. It is recommended that further investigation of the study be integrated into communication media which is appropriate to the needs of the students.